혈청 알파태아단백치가 현저히 상승한 대장암의 간전이 1예 - 윤탁; Tae Yoon; 안민; Min An; 신정아; Jeong A Shin; 이상민; Sang Min Lee; 박원서; Weon Seo Park; 최준일; Joon Il Choi; et al. (Clinical and molecular hepatology, 2006)
알파태아단백(AFP)은 태생기에 많이 생산되는 단백으로 출생 이후에는 현저히 줄어드나 간세포 암종, 난황낭종양(yolk sac tumor), 배아세포종양, 간모세포종 등의 종양이 발생하면 특징적으로 상승한다. 특히 간세포암종의 종양표지자로서 선별 검사와 치료 효과 판정 및 재발의 평가에 유용하게쓰이므로 혈청 AFP치가 간세포암종 이외의 상황에서 증가하는 경우에는 그 의미를 정확히 밝히는 것이 감별진단의 요체가 된다. 만성 간염 및 간경변증에서 간혹 혈청 AFP치의 상승이 관찰되지만 그 수준은 높지 않은 경우가 대부분이다. 간외 원발 소화기암에서1-4 혈청 AFP치의 상승이 간혹 발견되긴 하지만 대장암에서 혈청 AFP의 상승은 극히 드문 것으로 알려져 있다.5,6 이에 저자들은 만성 간염 및 간경변증 없이 혈청 AFP의 현저한 상승을 보였던 대장선암종의 다발성 간전이 1예를 경험하여 문헌 고찰과 함께 보고하고자 한다. We report herein a case of 72-year-old woman in whom liver metastasis of colon cancer was presented with a marked elevation of serum alpha-fetoprotein (AFP) level. She was transferred to our hospital for multiple liver masses found on ultrasonogram. Abdominal computed tomogram revealed multiple low-density masses in the liver and wall thickening of the hepatic flexure of colon. The serum AFP level was 10,718.8 ng/mL. Colonoscopic findings of ulcerofungating mass suggested liver metastasis from colon cancer. However, the possibility of combined hepatocellular carcinoma could not be ruled out due to serum AFP elevation. Both colon and liver biopsies revealed moderately differentiated tubular adenocarcinoma. Using an immunohistochemical staining, the adenocarcinoma in liver showed focal positive to AFP, but not in colon. This case represents a very rare case of colon cancer with a marked elevation of serum AFP. KCI Citation Count: 0